Artificial Intelligence in Healthcare: Between Potential and Risks - FAHMI , Asmaa; ECHAOUI, Abdellah (Revue Internationale du Chercheur, 2025)
abstract Artificial intelligence (AI) is a rapidly evolving technology that has attracted substantial interest from researchers across multiple disciplines, owing to its potential to profoundly reshape all sectors of society, including healthcare. In this context, we sought to evaluate physicians' perceptions of AI integration into clinical practice. To this end, a survey was conducted among doctors at the Children’s Hospital to gather their views on the potential applications of AI in medical settings. The results indicate that 86% of physicians recognize AI’s potential to enhance diagnostic accuracy, improve time efficiency by allowing greater focus on patient care, and support clinical decision-making. Nevertheless, 13.6% of respondents expressed reservations or uncertainty regarding these potential benefits. While the majority view human-machine collaboration positively, it remains crucial to address the risks and challenges associated with AI in healthcare. These include concerns related to medical ethics, the reliability of automated diagnoses, and the safeguarding of patient data.